THE EFFECTIVENESS OF ADMINISTRATIVE CONTROL IN FACING HARASSMENT OF WOMEN IN IRAQ - Abd Al-Hadi, Maysoon Ali (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT–States shall endeavor to achieve security and order in society and, for that purpose, may follow certain measures aimed at establishing order and security in society as well as providing the necessary services to citizens and the public interest. The State shall, through its legislative, executive and judicial powers, exercise an activity aimed at achieving stability under the public order and its elements related to public security, public health, public tranquility and public morals. If such activities or procedures are pursued by the authorities of the State as a whole, the laws are the responsibility of the executive branch as its bodies carry out duties that are in touch with daily life and behavior of individuals. Therefore, the administrative control bodies, specifically the Ministry of the Interior, are the closest to achieving what is called administrative discipline in the special sense. good law enforcement and confront crimes and phenomena contrary to morality or disrupt public order in the event of their increase and the phenomenon of its example harassment of women.